Upacara Nepu Wie Dalam Perbandingan Dengan Devosi Kristiani - Nampar, Hilario Didakus Nenga (Perspektif, 2014)
The writer argues that the traditional rite of nepu wie of Kuku Mese society (Nagekeo, Flores) has a very deep meaning for the whole society. The nepu wie rite is basically a ritual for the dead ones performed by their family primarily for their incorporation into the community of the ancestors. The writer explains that the nepu wie rite has some similarities with the devotion to the saints in the Catholic tradition. The article describes some meeting points as well as the differences of the two traditions and, then, intentionally attempts to give the nepu wie rite a Christian meaning. The writer finally comes to the conclusion that basically there is no obstacle for the Catholics of Kuku Mese society to perform the rite of nepu wie as the important part of their devotion to their ancestors.